2017
DOI: 10.18203/2320-6012.ijrms20173697
|View full text |Cite
|
Sign up to set email alerts
|

An aetiological evaluation of short stature

Abstract: Background: Short stature can be a normal variant or secondary to an underlying disorder. It is necessary to evaluate short stature to differentiate a normal from pathological short stature and thus decide the further treatment needed. This study was conducted at a tertiary care hospital to find out the various etiologies of short statureMethods: An observational study was conducted on 49 children in age of 2-12 years with short stature. They were grouped as normal variants and pathological short stature depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
(12 reference statements)
1
5
1
Order By: Relevance
“…In our study the endocrine causes for short stature was 18% whose findings are consonant with other research like Rabbani et al (15.9%) and Phirke (12.24%). [1,14] Endocrine causes were low in Shiva ) which are conflicting to our study. [15,19,20,[24][25][26] This may be due to the difference of study settings where each study is being done.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…In our study the endocrine causes for short stature was 18% whose findings are consonant with other research like Rabbani et al (15.9%) and Phirke (12.24%). [1,14] Endocrine causes were low in Shiva ) which are conflicting to our study. [15,19,20,[24][25][26] This may be due to the difference of study settings where each study is being done.…”
Section: Discussioncontrasting
confidence: 90%
“…In our study, among pathologic short stature, malnutrition (9%) was found to be the most common non endocrinological cause. These results were consistent with [14,[23][24][25]27,28] Other causes like genetic syndrome constitute 5 % of short stature which is in consonant with many Indian studies done by Bhadada et al (7.4%), Phirke et al (4%) and Deep Dutta et al(8%). [14,18,27] The shortcomings of this study include failure to calculate and plot growth velocity which requires a regular follow-up at six months to twelve months interval, which was not possible in this cross-sectional study.…”
Section: 3% In Our Study 19% 18%supporting
confidence: 87%
See 2 more Smart Citations
“…Among them, 24% had systemic cause where as malnutrition and endocrine cause was found in 12 % each. 15 The infancy phase of growth which has been assumed to begin at mid gestation and taper off around 2 to 3 years is regarded as predominantly nutrition dependent.11 Malnutrition at this phase of growth can lead to stunted growth.…”
Section: Introductionmentioning
confidence: 99%